Synaptotagmin-1 membrane binding is driven by the C2B domain and assisted cooperatively by the C2A domain - Gruget, Clémence (2020)
Synaptotagmin interaction with anionic lipid (phosphatidylserine/phosphatidylinositol) containing membranes, both in the absence and presence of calcium ions (Ca2+), is critical to its central role in orchestrating neurotransmitter release. The molecular surfaces involved, namely the conserved polylysine motif in the C2B domain and Ca2+-binding aliphatic loops on both C2A and C2B domains, are known. Here we use surface force apparatus combined with systematic mutational analysis of the functional surfaces to directly measure Syt1-membrane interaction and fully map the site-binding energetics of Syt1 both in the absence and presence of Ca2+. By correlating energetics data with the molecular rearrangements measured during confinement, we find that both C2 domains cooperate in membrane binding, with the C2B domain functioning as the main energetic driver, and the C2A domain acting as a facilitator.